(untitled) (Progressive Agriculture, 2016)
Sustainable development in potato production is an issue of growing concern. Today, population growth, the need to further the cause of human food, agricultural and energy development in the agriculture sector is. Excessive consumptionof food demand huge population the lack of stability in the future willproduce. The effect of planting technique on the yield of potato at charland ecosystem has been investigated. A field experiment was conducted at the MLT site Ulipur during rabi season 2012-13 and 2013-14 to observe the suitable planting techniques on tuber yield of potato at charland ecosystem. Four planting techniques viz., recommended system of planting (60cm×30cm), Single eye planting(30cm×10cm), Single eye double row zigzag system(10cm/30cm×10cm), and Half cut system(30cm×10cm), were evaluated for this purpose. The experiment was laid out in a randomized complete block design with six dispersed replications. Among the tested planting techniques, the highest tuber yield (29.0 t ha-1) was obtained from recommended system of planting and the lowest yield was obtained from single eye planting (22.5t ha-1) system. The highest gross return (Tk.217500 ha-1) and gross margin (Tk.75000 ha-1) were obtained from recommended system of planting. Progressive Agriculture 27 (2): 144-148, 2016